Sejarah Perkembangan Ilmu Pengetahuan Dan Teknologi Dalam Islam - Ichwani, Imron; Firmaningrum, Farroha (Universitas Cokroaminoto Yogyakarta, 2023)
Observing and researching the historical periodization of the growth of science and technology in Islam is the aim of this study. This study uses descriptive analysis which is complemented by a historical analysis approach in conducting library research. The direction of knowledge or data interpretation is prioritized on a historical approach. The research findings show that as science and technology progress today, they are increasingly related to one another. Islam refers to this as the integration of science and technology with the Al-Qur'an which is the main text for this integration and then followed by Hadith as the second proposition after the Al-Qur'an.